Karya Tari Sang Kustiah Refleksi Perempuan pada Masa Kini - Wisnu Pamenang, Nandhang; Dewi, Maharani Luthvinda; Samsuri, Samsuri (Acintya, 2023)
Kustiah’s dance works contain values and can be used as a reference in current and future life. One of them is that Kustiah’s dance work includes the importance of Unity, Creativity, Tough, and Abstinence, which are philosophical teachings that are upheld and can serve as role models for women at this time in moving forward in their lives. This value can be adhered to and carried out, ultimately giving women a strong character and soul.Keywords: Dance work, Kustiah, reflextion, women.